Pilgirmguard band: pilgrimage emergency bracelet - Ashan, Mohd Zulfahmi; Francis, Debra Utih; Dominic, Floria Ann; Pilem, Stephanie; Fatt, Boyd Sun (Universiti Teknologi MARA, Kedah, 2023)
Every year, Muslims travel to Mecca and Medina to perform the religious pilgrimage of Hajj and Umrah. Approximately 4.8 million individuals visited Mecca and Medina (2022). However, the large turnout resulted in several unforeseen incidents during the event. In this context, it is crucial to prioritize safety during Hajj and Umrah. In numerous studies, unexpected occurrences often arise, such as the loss of participants or individuals, fainting due to overcrowding, and other similar incidents. This highlights the difficulties encountered by individuals participating in Hajj and Umrah during the performance of these religious pilgrimages. The researcher made a decision to create a bracelet that would aid in facilitating a smoother and safer pilgrimage experience. The researcher proposed the concept of an emergency bracelet called PilgrimGuard Band. This bracelet is specifically designed for individuals participating in Hajj and Umrah who are visiting Mecca and Medina during their journey. It serves as an emergency tool. The Hajj and Umrah experience will be made easier for participants with the inclusion of several interesting features. With PilgrimGuard Band present, the safety of all participants will be closely monitored and any untoward incidents will be promptly addressed. The tour guide or tour operator will provide participants who performHajj and Umrah with an emergency bracelet.